Chromium Phytoremediation of Tannery Wastewater using Ceratophyllum demersum - Suryani, Yani; Cahyanto, Tri; Sudjarwo, Toni; Panjaitan, Diana Vici; Paujiah, Epa; Jaenudin, Mohamad (Biosaintifika: Journal of Biology & Biology Education, 2017)
Tanning industry produces liquid waste containing heavy metals, especially chromium harmful for ecosystems and human health. Phytoremediation is a technique that utilizes the physiologicalpotential of plants to transform contaminants to be less or non-hazardous. The aim of the research is to determine the efficiency of Ceratophyllum demersum L. to remediate chrome in tannery wastewater. The research used 84 strands of C. demersum compound leaves of 30 g wet weight. The treatments consist of the use of 7.74 mg/L, 11.30 mg/L, 17.00 mg/L and 23.73 mg/L concentrations of chromium and a control. The research was conducted using a static method. The design of the experiment was the complete random design with 3 replication of treatment in 14 days. The parameters observed were the efficiency of chromium phytoremediation, water turbidity, BOD, and total chlorophyll level of the leaves. The results showed that the highest efficiency was at the concentration of 7.74 mg/L with 1.7% chromium, 17.3% water turbidity, and 46% BOD. Meanwhile, the highest efficiency of total chlorophyll level was 3.88 mg/L, reached at the concentration of 17.00 mg/L. In conclusion, C. demersum is good to use as a phytoremediator of tannery wastewater at the concentration of 7.74 mg/L, subsequently, these results can be used as a basis for the consideration of the application implementation in the process of liquid waste reduction.